Oleic Acid Increases Synthesis and Secretion of VEGF in Rat Vascular Smooth Muscle Cells: Role of Oxidative Stress and Impairment in Obesity - Doronzo, Gabriella (MDPI, 2013)
Obesity is characterized by poor collateral vessel formation, a process involving vascular endothelial growth factor (VEGF) action on vascular smooth muscle cells (VSMC). Free fatty acids are involved in the pathogenesis of obesity vascular complications, and we have aimed to clarify whether oleic acid (OA) enhances VEGF synthesis/secretion in VSMC, and whether this effect is impaired in obesity. In cultured aortic VSMC from lean and obese Zucker rats (LZR and OZR, respectively) we measured the influence of OA on VEGF-A synthesis/secretion, signaling molecules and reactive oxygen species (ROS). In VSMC from LZR we found the following: (a) OA increases VEGF-A synthesis/secretion by a mechanism blunted by inhibitors of Akt, mTOR, ERK-1/2, PKC-beta, NADPH-oxidase and mitochondrial electron transport chain complex; (b) OA activates the above mentioned signaling pathways and increases ROS; (c) OA-induced activation of PKC-beta enhances oxidative stress, which activates signaling pathways responsible for the increased VEGF synthesis/secretion. In VSMC from OZR, which present enhanced baseline oxidative stress, the above mentioned actions of OA on VEGF-A, signaling pathways and ROS are impaired: this impairment is reproduced in VSMC from LZR by incubation with hydrogen peroxide. Thus, in OZR chronically elevated oxidative stress causes a resistance to the action on VEGF that OA exerts in LZR by increasing ROS.